An exergy-based analysis of the effects of public incentives on the so-called “energy efficiency” of the residential sector, with emphasis on primary resource use and economics of scale - Biondi, Alfonso; Caponi, Piermaria; Cecere, Carlo; Sciubba, Enrico (Frontiers in Sustainability, 2024)
Improving building efficiency is essential for reducing final energy use, greenhouse gas emissions, and operational costs. The average share of the Residential/Commercial Sector for space conditioning accounts for 30-37% of the cumulative final energy use in OECD Countries . Therefore, some governments have resolved to launch incentivization campaigns to encourage private and public actors to invest in building efficiency. This strategy was successful as its large-scale application -even if enacted on a preliminary basis- led to significant reductions of the energy load per square meter. It is likely that such subsidies will assume a major role in shaping the construction market. Technologies deemed "more environmental benign" or "of strategic interest" receive institutional funding to promote their implementation, the funds being allocated both to design techniques, new materials and less energivorous devices. Since the funding is usually provided in the form of tax rebates, this approach is not devoid of problems: in fact, previous campaigns at regional and national level in the primary Energy Conversion and in the Transportation Sector have resulted in monumental failures. While it is clearly in the interest of a community to enact a reduction of its final energy uses, it is true that such incentivization plans, if not properly and carefully implemented, may constitute an economic and ecological "doping" of the market (detail price increases, material and components shortages...). This paper is a follow-up of a previous study conducted in 2021-22 that proposed a rational and thermodynamic based approach to the issue that included an innovative cost/benefit procedure. In this approach, the implementation costs of an "energy saving" or seismic intervention are first combined (improvement of the building energy and seismic class) and then compared with the savings originated in a given operational window. The method is intended to serve as a possible model for future policy decisions, and it makes use of the fundamental principles of Exergy Analysis augmented by a conventional cost/benefit analysis and by basic resilience considerations. The case study analysed in a previous paper is re-examined here in the light of some more recent data released for public use in spring 2024